The Contribution of α-Synuclein Spreading to Parkinson's Disease Synaptopathy. (3rd January 2017) - Longhena, Francesca; Faustini, Gaia; Missale, Cristina; Pizzi, Marina; Spano, PierFranco; Bellucci, Arianna
Abstract : Synaptopathies are diseases with synapse defects as shared pathogenic features, encompassing neurodegenerative disorders such as Parkinson's disease (PD). In sporadic PD, the most common age-related neurodegenerative movement disorder, nigrostriatal dopaminergic deficits are responsible for the onset of motor symptoms that have been related to α -synuclein deposition at synaptic sites. Indeed, α -synuclein accumulation can impair synaptic dopamine release and induces the death of nigrostriatal neurons. While in physiological conditions the protein can interact with and modulate synaptic vesicle proteins and membranes, numerous experimental evidences have confirmed that its pathological aggregation can compromise correct neuronal functioning. In addition, recent findings indicate that α -synuclein pathology spreads into the brain and can affect the peripheral autonomic and somatic nervous system. Indeed, monomeric, oligomeric, and fibrillary α -synuclein can move from cell to cell and can trigger the aggregation of the endogenous protein in recipient neurons. This novel "prion-like" behavior could further contribute to synaptic failure in PD and other synucleinopathies. This review describes the major findings supporting the occurrence of α -synuclein pathology propagation in PD and discusses how this phenomenon could induce or contribute to synaptic injury and degeneration.